Folklore in the United States and Canada : an institutional history - Sawin, Patricia; Zumwalt, Rosemary Levy (Indiana University Press, 2020)
To ensure continuity and foster innovation within the discipline of folklore, we must know what came before. Folklore in the United States and Canada is an essential guide to the history and development of graduate folklore programs throughout the United States and Canada. As the first history of folklore studies since the mid-1980s, this book offers a long overdue look into the development of the earliest programs and the novel directions of more recent programs. The volume is encyclopedic in its coverage and is organized chronologically based on the approximate founding date of each program. Drawing extensively on archival sources, oral histories, and personal experience, the contributors explore the key individuals and central events in folklore programs at US and Canadian academic institutions and demonstrate how these programs have been shaped within broader cultural and historical contexts. Revealing the origins of graduate folklore programs, as well as their accomplishments, challenges, and connections, Folklore in the United States and Canada is an essential read for all folklorists and those who are studying to become folklorists.